(untitled) (Journal of the College of Education for Women, 2023)
The current research’s problem includes the impact of cognitive reappraisal and reformulate on self-experience of emotional response and its negative feelings and the activity of cognitive reappraisal in changing response. The aim of this research is to detect the relation between adaptive response and cognitive reappraisal upon students of secondary school, and to find differences in gender and stage. The sample contained male and female student for the year(2022-2023) and consists of (480) students (240) male and (240) female in the karkh education/ 1 To achieve this aims researcher used descriptive method and to measure the two variables researcher built a scale for adaptive response according to theory of compound emotion (Barrett,2015) contains (31) items , and the scale of cognitive reappraisal according to the theory of (Lazarus,1991) contains (30) items credit to scientific steps for building psychometric properties , validity , virtual validity by presenting them to a number of experts,and the constructive validity in the light of relation between item and total grade. Reliability was lasted by Vaccronbach coefficient. After treating data by (SPSS), researcher found that students have adaptive response and cognitive reappraisal,and there is assign efficient relation between adaptive response and cognitive reappraisal, and there are significant difference in cognitive appraisal according to grade in favor of the fifth grade at (0.05). Researcher recommends the importance of adaptive response and reappraisal for their relation with (IQ), school performance, social skills, adaptive behavior, and make a comparison studies to detect adaptive response and cognitive reappraisal upon other school students and college students that help to adapt with academic atmosphere, coping with problems, and reduce stress.